Chapter Ships, shipping, technological change and global economic growth, 1400-1800 - Unger, Richard W. (Datini Studies in Economic History, 2023)
The major breakthrough in ship design around 1400 creating the full-rigged ship constituted a general purpose technology. It had far-reaching effects on shipping, trade volume, orientation of trade routes, location of production, settlement patterns and many other aspects of life throughout the globe from 1400 to1800. The greater efficiency of the type in a number of uses led to its dissemination, to a limited degree, throughout the world. Spillovers from the success of the design were extensive and included for example a literature on designing and building ships, improvements in navigation and in government practices. Advances in shipbuilding were one of the very few technologies in the period that qualified as a technological advance with massive consequences.